Health, healing and religion: an African view - Pobee, John S. (International Review of Mission, 2001)
My invitation was to read a paper on "Health, healing and religion as understood and practised in Asian or African cultures". I have taken the "or" in the assigned topic seriously not only because I am not confident to wax eloquently on Asia but also because of time constraints. However, there is a deeper reason: it is not unusual to treat the so-called South, third world or developing world as one block over against the North or first world or developed world. Such efforts tend to miss out on the "all sorts and conditions" of the so-called third world, with the result that solutions emerging from such broad generalizations time and again either do not satisfy anyone or prove impracticable in many a third world region.
paid
Keywords: Africa – Religion; Christianity and African religions; Healing; Spirits; Witchcraft